Robust attitude coordinated control for spacecraft formation with communication delays - Hu, Qinglei (2017)
In this paper, attitude coordinated tracking control algorithms for multiple spacecraft formation are investigated with consideration of parametric uncertainties, external disturbances, communication delays and actuator saturation. Initially, a sliding mode delay-dependent attitude coordinated controller is proposed under bounded external disturbances. However, neither inertia uncertainty nor actuator constraint has been taken into account. Then, a robust saturated delay-dependent attitude coordinated control law is further derived, where uncertainties and external disturbances are handled by Chebyshev neural networks (CNN). In addition, command filter technique is introduced to facilitate the backstepping design procedure, through which actuator saturation problem is solved. Thus the spacecraft in the formation are able to track the reference attitude trajectory even in the presence of time-varying communication delays. Rigorous analysis is presented by using Lyapunov-Krasovskii approach to demonstrate the stability of the closed-loop system under both control algorithms. Finally, the numerical examples are carried out to illustrate the efficiency of the theoretical results.